PERAN TOKOH AHMADIYAH TERHADAP PELESTARIAN ADAT DAN TRADISI SOSIAL PENGANUT AHMADIYAH DI KOTA MEDAN - Pertiwi, Suci Indah; Susanti, Neila; Jailani, Muhammad (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
Apart from the six religions that were formalized in the country of Indonesia there are many beliefs, religious schools and ancestral religions believed by some residents of the city of Medan, one of which is Ahmadiyah which is a religious sect originating from Qadiran India, Ahmadiyah has several adherents in the city of Medan and belongs to the in the minority category. So, the formulation of the problem in this research is What is the Role of Ahmadiyya Figures in Preserving Ahmadiyya Adherents' Customs and Social Traditions in Medan City. The use of research forms in this study is qualitative research. In using descriptive research, the problem used as the formulation of the problem is included in the category worthy of being raised, namely the problem contains scientific value, is not too broad, the goal cannot be too broad and uses data that is factual not opinion. With data collection techniques that is conducting interviews, observation and documentation. The Role of Ahmadiyya Leaders in Preserving Customs and Social Traditions of the Ahmadiyya in Medan City There are several roles played by the Ahmadiyya religious leaders in preserving social customs and traditions, namely by respecting and following local government laws and mechanisms, both those based on positive law dan Islamic.